Sensitivity of the negative ion beam extraction to initial plasma parameters by 3D particle modelling. (1st December 2022) - Lindqvist, Max; Wünderlich, Dirk; Mimo, Alessandro; Mochalskyy, Serhiy; Revel, Adrien; Nocentini, Riccardo; Minea, Tiberiu; Fantz, Ursel
Abstract: The ITER neutral beam injection system for heating and current drive requires Negative Ions (NI) produced in large ceasiated ion sources. Self-consistent 3D Particle-In-Cell Monte-Carlo Collision (PIC-MCC) modelling is necessary for simulating extraction of NI and the co-extraction of electrons in ITER-like ion sources. In the RF driven negative ion sources at the ELISE and BUG test facilities, the filter field is generated by a current drawn through the Plasma Grid (PG). The 3D PIC-MCC code ONIX has been used to study the role of electron temperature, plasma density and emission rate on the extracted currents, as well as the negative ion transport close to an extraction aperture of the PG in ELISE. The results are compared to a case with higher electron density, lower electron temperature and higher emission rate, corresponding to the typical working point of a filter field configuration generated by permanent magnets. It is shown that the current of co-extracted electrons is strongly influenced by the electron temperature and plasma density. Increasing T e from 1 eV to 2 eV and decreasing the plasma density lead to an increase of co-extracted electrons by a factor 4 due to the increased electron flux towards the aperture and a deeper penetration of the extraction potential into the plasma. With reduced plasma density, the fraction of NI extracted directly after production on the PG increases. An additional parameter variation was conducted to study the effect of the emission rate of NI on the extracted currents. A reduced emission rate of NI from the PG from 550 Am −2 to 200 Am −2 reduces the extracted negative ion current by ∼ 40 Am −2 due to a reduction of the number of directly extracted NI.